Robson Criteria to Determine the Risk of Cesarean Section in Females Presenting to Sir Ganga Ram Hospital (SGRH), Lahore: Robson Classification and Caesarean Section Rates - Haider, Shazia; Zahid, Hafiza Mariam; Nawaz, Asma; Fatima, Musarrat; Jamil, Bushra; Yousaf, Anum; Kanwal, Sibgha; Ahmad, Sajjad; Kanwal, Seep (Pakistan Journal of Health Sciences, 2024)
Rates of caesareans have increased, resulted in unfavourable outcomes in subsequent pregnancies. Robson categorization enhances standard of care by optimising the use of C-sections and evaluating methods to lower caesarean rates. Objective: To determine the frequency of caesarean section and to determine frequency of Robson 10 group classification system in patients who undergo caesarean. Methods: In this cross-sectional study, 140 pregnant selected via simple random sampling, were enlisted from Gyne department of SGRH, Lahore. According to Robson 10-group categorization those who underwent C-section were divided into ten groups and indication of C-section was studied. Data scrutiny was done using SPSS version 26.0. Mean and SD was used for quantitative variables and frequency for qualitative data. Data were stratified for effect modifiers, p-≤0.05 was taken as significant. Results: Mean age of patients calculated was 31.94 ± 2.14 years. Out of 140, 23.6% had C-section and 76.4% had vaginal delivery. According to class of modified Robson criteria, 12.1% had class 1, 12.1% had class, 2, 21.2% had class 3, 36.4% had class 5, and 3.0% each had class 4, 6, 7, 8, 9, and 10. Conclusions: According to our findings, considerable percentage of C-sections occur with previous C-sections serving as most common indicator. This pattern emphasizes how crucial it is to concentrate on primary preventive techniques in order to lower its rate. Large number of C-sections performed on nulliparous both those in spontaneous labour and those who were not indicates that labour management procedures and decision-making processes need to be closely examined.